2014
DOI: 10.1186/2046-7648-3-15
|View full text |Cite
|
Sign up to set email alerts
|

The impact of submaximal exercise during heat and/or hypoxia on the cardiovascular and monocyte HSP72 responses to subsequent (post 24 h) exercise in hypoxia

Abstract: BackgroundThe aims of this study were to describe the cellular stress response to prolonged endurance exercise in acute heat, hypoxia and the combination of heat and hypoxia and to determine whether prior acute exposure to these stressors improved cellular tolerance to a subsequent exercise bout in hypoxia 24 h later.MethodsTwelve males (age 22 ± 4 years, height 1.77 ± 0.05 m, mass 79 ± 12.9 kg, VO2 max 3.57 ± 0.7 L · min-1) completed four trials (30-min rest, 90-min cycling at 50% normoxic VO2 max) in normoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
2
32
1
Order By: Relevance
“…2). This observation varies slightly from that of a recent study in which a 53 % increase in iHsp72 concentration was demonstrated immediately following exercise in the heat and accompanied by a 30 % elevation in the basal level 24 h after exercise (Lee et al 2014). Previous studies examining the role of heat acclimation on the iHsp72 response have also shown an increase in the basal concentration of iHsp72 after 3-11 days of exposure to heat stress (Yamada et al 2007;McClung et al 2008;Magalhaes et al 2010;Lee et al 2015).…”
Section: Resultscontrasting
confidence: 72%
“…2). This observation varies slightly from that of a recent study in which a 53 % increase in iHsp72 concentration was demonstrated immediately following exercise in the heat and accompanied by a 30 % elevation in the basal level 24 h after exercise (Lee et al 2014). Previous studies examining the role of heat acclimation on the iHsp72 response have also shown an increase in the basal concentration of iHsp72 after 3-11 days of exposure to heat stress (Yamada et al 2007;McClung et al 2008;Magalhaes et al 2010;Lee et al 2015).…”
Section: Resultscontrasting
confidence: 72%
“…Consequently, exercise heat stress still appears to be the superior intervention (of those tested within the current experimental design) to increase Hsp72 and Hsp90␣ mRNA, at least within leukocytes and, therefore, potentially confer HSP72-and HSP90␣-mediated thermotolerance (39). Induction of HSP72 protein also occurs within monocytes following exercise within an hypoxic environment (32). Future studies are required to assess whether exercise heat stress and hypoxia (singularly and in combination) are the superior intervention to induce HSP72 and HSP90␣ within an experimental design, where metabolic strain is controlled more precisely.…”
Section: Practical Applications and Future Directionsmentioning
confidence: 87%
“…However, the current study cannot suggest that downhill running or exercise in hot environments can translate this signal into HSP72-mediated thermotolerance within leukocytes because increased Hsp72 mRNA expression is not necessarily reflective of functional steady-state HSP72 content (38,66). Any HSP72 increases that were potentially induced by downhill running or exercise in a hot environment would not have had a confounding effect on the Hsp72 and Hsp90␣ mRNA responses, as HSP72 increases are sustained for less than 7 days within leukocyte subsets (monocytes) (18,32).…”
Section: Leukocyte Hsp72 Mrnamentioning
confidence: 98%
“…However, our pilot testing revealed a longer occlusion period was not tolerable in vivo by non-anesthetized humans thus precluding its implementation. In an exercise setting, variants of our IPC (de Groot et al, 2010 ; Bailey et al, 2012 ; Cruz et al, 2015 ; Kido et al, 2015 ; James et al, 2016 ; Sabino-Carvalho et al, 2016 ), and HPC (Lee et al, 2014 ; Turner et al, 2016 ; Chacaroun et al, 2017 ), have been implemented to induce positive physiological responses. These data reflecting positive responses in clinical paradigms (Landry et al, 1982 ; Tomai et al, 1999 ; Otani, 2008 ; Mateika et al, 2014 ; Verges et al, 2015 ; Baillieul et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A standardized meal [cornflakes (50 g), milk (250 mL), and 1 l of water], as employed by others (Foster et al, 2016 ), was utilized within the experimental design. Relative to HSP and OS outcome variables, their between- and within-subject variation is established at rest (Fisher-Wellman and Bloomer, 2009 ; Sandström et al, 2009 ; Taylor et al, 2010b ) and in response to stressors (Hillman et al, 2011 ; Lee et al, 2014 ; Peart et al, 2015 ). Accordingly an array of robust and previously employed experimental controls were incorporated within the study design to control for the confounding influences on HSP and/or OS responses of smoking (Anbarasi et al, 2006 ), caffeine (Whitham et al, 2006 ), glutamine (Wischmeyer et al, 2001 ; Zuhl et al, 2015 ), alcohol (Wu and Cederbaum, 2003 ), dietary consumption (Kuennen et al, 2011 ; Marshall et al, 2017 ), fluid intake (attainment of euhydration; Logan-Sprenger et al, 2015 ), generic supplementation (Pingitore et al, 2015 ), prior exercise (Lee et al, 2014 ), previous environmental (hypoxia and heat) exposures (Gibson et al, 2015b ; Lee et al, 2016 ), and diurnal variation in basal HSP (Taylor et al, 2010a , b , 2011 , 2012 ; Hillman et al, 2011 ; Costa et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%